Islamic Press in Surakarta (914-1926): A Study of Medan Moeslimin and Islam Bergerak - Nor Huda Ali; Moh. Ashif Fuadi; Moh. Mahbub; Kamila Adnani (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2023)
This study describes the changing function of two Islamic presses, namely Medan Moeslimin and Islam Bergerak, in Surakarta, Central Java, Indonesia, in the transition of the 19th and 20th centuries. By historical methods through newspaper archival sources, the study produced conclusions; first, these two media were initially used as a means to “defend Islam” from some articles in the media that blasphemed Islam and, at the same time, straightened it out. In addition, the two Islamic media became an alternative source of Islamic scholarship, especially among reformist-modernist Muslims. Second, the two media were loaded with ideological interests. In their development, they had shifted their orientation from “defenders of Islam” to defenders of the spirit of nationality and universal humanity. Third, the change in orientation was inseparable from the critical role of Hadji Mohammad Misbach (1876-1926), the owner and manager of the two media, who experienced an ideological shift from orthodox Muslim towards socialist and nationalist one at once.